2019
DOI: 10.18203/2349-3291.ijcp20190684
|View full text |Cite
|
Sign up to set email alerts
|

Study of foot length as an alternate measurement for assessment of gestational maturity in neonates

Abstract: Background: The aim was to study neonatal foot length as a simple method for quick gestational age assessment which can be done by basic healthcare personnel overcoming the technicality required by other assessment methods.Methods: Prospective descriptive study was done. Live born neonates at Saveetha Medical College, Kanchipuram from June 2016 to June2017 were enrolled. Gestational age was assessed by New Ballard’s Scoring and footlength was measured using the paddle blades of automated digital Vernier calipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…Some used LMP (18), some used ultrasound examination (20), some used clinical examination (19), and some used the Ballard score for assessing GA. (16) Similarly, foot length was measured using different measuring equipment. The most commonly used equipment was a Vernier caliper (16,17,19,20), followed by transparent rigid scales and steel or exible tapes. (10,18,21) The unit of measurement was also different across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some used LMP (18), some used ultrasound examination (20), some used clinical examination (19), and some used the Ballard score for assessing GA. (16) Similarly, foot length was measured using different measuring equipment. The most commonly used equipment was a Vernier caliper (16,17,19,20), followed by transparent rigid scales and steel or exible tapes. (10,18,21) The unit of measurement was also different across studies.…”
Section: Discussionmentioning
confidence: 99%
“…(10,18,21) The unit of measurement was also different across studies. Some used centimeters (16)(17)(18) and some millimeters. (19-21) However, almost all studies measured foot length from the mid-point of thê heel to the longest toe.…”
Section: Discussionmentioning
confidence: 99%
“…For validation, the foot length of Pakistani neonates for estimating GA was assessed using regression equations reported by different studies (16)(17)(18)(19)(20)(21). The mean difference between observed and predicted GA was compared using a paired t-test.…”
Section: Discussionmentioning
confidence: 99%
“…Streeter et al in 1920, rst observed that the foot length co be used as a proxy for estimation of GA. 15Many studies since then have shown a positive linear relationship between GA and foot length. (16)(17)(18)(19)(20)(21) However, the coe cient of determination (r 2 ) of foot length and GA is different in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation